Limites e possibilidades da Lei do Feminicídio enquanto medida concretizadora dos direitos fundamentais das mulheres que se encontram em situação de violência. - Ponte, Sarah Venâncio (2019)
The violence against women is a debated phenomenon in Brazil. And, in March 2015, Law nº 13.104, which creates the category of femicide, was sanctioned, with the inclusion of a qualifier in the type of homicide, when it is practiced "by female conditions." In this sense, it is intended to answer whether the use of a penal sanction (punitive bias) is a measure capable, in itself, notably in a Democratic State of Law, to guarantee the social purpose of the Law, which is to restrain gender violence, by reducing the number of homicides of women, all for the woman to become a creditor of rights. To do so, initially, the research was based on understanding the construction of the phenomenon of gender violence that culminated in the current and extensive apparatus of legislative protection for women, but pointing to a historical incapacity of the Right to transform this reality. Next, we will discuss the term femicide, with an exposition about the emergence of this category and the debates in the literature on the subject, also explaining its typology and how it became popular in Latin America, besides the characteristics of some of these legislations in relation to the Brazilian, since those inspired this. On the other hand, in a third section of the dissertation, the Brazilian Femicide Law will be studied, with the exploration of the context, in which it was developed, besides its motivation, structure and objectives, from which can ascertain the answers intended by Law nº 13.104/2015 on the issue of sexist killings against women and the major doctrinal criticisms of the criminal response. On the other hand, Chapter 4 discusses what has been exposed in the research so far, starting with the function of criminal sanction in a Democratic State of Law, in order to problematize the application of Criminal Law as an instrument of State power and as a means of public policy for the realization of Women's Fundamental Rights. It seeks to prove the hypotheses, correlating empirical data (number of deaths of women before and after the new law) with the theoretical references developed in the text. The research was qualitative regarding the approach; applied regarding the nature; descriptive and explanatory, regarding the objectives; documentary and bibliographical, regarding to the procedures. Finally, it is intended to assert that the construction of women’s dignity does not pass only by legislative changes, especially those of a criminal nature, which are only symbolic and unskilled, by themselves, for the solution of the problematic. But on the contrary, it demands different alternatives and changes of another order, as in education, with the construction of a new culture that surpasses the historical conception of gender as we contemplate today.